Implementation of the Electronic Criminal Case File Transfer System - Desi Apriguna Singarimbun; Kartina Pakpahan (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The aim of the research is to find out the implementation mechanism for the electronic criminal case file transfer system, legal review and supporting and inhibiting factors for the implementation of the electronic criminal case file transfer system at the Binjai District Court. This research method uses empirical law, empirical law (empirical legal research), which is a type of legal research that analyzes and studies the operation of law in society. The results of electronic research into Integrated Criminal Files (e-Berpadu) are the Integration of Criminal Files between Law Enforcement Agencies. The Law Enforcement Agencies in question are the Police, Prosecutor's Office, Institution Correctional and District Courts throughout Indonesia. The e-Berpadu application is here to realize the digitization of Criminal Case Administration and cut long bureaucratic procedures to create effectiveness and efficiency service criminal cases which are expected to improve services for people seeking justice. However, in the process there are still obstacles such as applications that have not been well socialized, lack of professional human resources and Not yet the public of every party related to the system.